Omentin functions to attenuate cardiac hypertrophic response. (February 2015) - Matsuo, Kazuhiro; Shibata, Rei; Ohashi, Koji; Kambara, Takahiro; Uemura, Yusuke; Hiramatsu-Ito, Mizuho; Enomoto, Takashi; Yuasa, Daisuke; Joki, Yusuke; Ito, Masanori; Hayakawa, Satoko; Ogawa, Hayato; et al.
Abstract: Cardiac hypertrophy occurs in many obesity-related conditions. Omentin is an adipose-derived plasma protein that is downregulated under obese conditions. Here, we investigated whether omentin modulates cardiac hypertrophic responses in vivo and in vitro . Systemic administration of an adenoviral vector expressing human omentin (Ad-OMT) to wild-type (WT) mice led to the attenuation of cardiac hypertrophy, fibrosis and ERK phosphorylation induced by transverse aortic constriction (TAC) or angiotensin II infusion. In cultured cardiomyocytes, stimulation with phenylephrine (PE) led to an increase in myocyte size, which was prevented by pretreatment with human omentin protein. Pretreatment of cardiomyocytes with omentin protein also reduced ERK phosphorylation in response to PE stimulation. Ad-OMT enhanced phosphorylation of AMP-activated protein kinase (AMPK) in the heart of WT mice after TAC operation. Blockade of AMPK activation by transduction with dominant-negative mutant forms of AMPK reversed the inhibitory effect of omentin on myocyte hypertrophy and ERK phosphorylation following PE stimulation. Moreover, fat-specific transgenic mice expressing human omentin showed reduced cardiac hypertrophy and ERK phosphorylation following TAC surgery compared to littermate controls. These data suggest that omentin functions to attenuate the pathological process of myocardial hypertrophy via the activation of AMPK in the heart, suggesting that omentin may represent a target molecule for the treatment of cardiac hypertrophy. Highlights: Systemic delivery of omentin to mice leads to the reduction of cardiac hypertrophy. Treatment of cardiac myocytes with human omentin protein reduces cellular hypertrophy. Omentin reduces hypertrophic responses of cardiac myocytes through AMPK activation. Fat-specific TG mice expressing human omentin show reduced cardiac hypertrophy.